2005
DOI: 10.1182/blood.v106.11.593.593
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Inhibit Generation and Function of Both Monocyte-Derived and CD34-Derived Dendritic Cells.

Abstract: Mesenchymal stem cells (MSCs) have been demonstrated to exert profound immunosuppressive properties on T cell proliferation. However, their effect on the initiators of the immune response, the dendritic cells (DCs), are relatively unknown. In the present study, the effects of MSCs on the differentiation and function of both monocyte-derived DCs and CD34+-derived DCs were investigated. Monocytes (CD1a-CD14+) were obtained from PB and were cultured with IL-4 and GM-CSF to induce differentiation into CD14-CD1a+ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
179
3
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(200 citation statements)
references
References 0 publications
5
179
3
13
Order By: Relevance
“…Several reports have shown that MSCs have the ability to interfere with DC differentiation and maturation, from both CD34 + bone marrow cells and CD14 + monocytes. 35,36 In this study we have shown that co-culturing of monocytes with UCMSCs prevented the CD14 + cells to differentiate and mature to DCs. Although the monocytes acquired antigens such as CD209, CD86 and B7-H1, all known to be expressed on imDCs, these cells failed to downregulate CD14 antigen in the presence of UCMSCs.…”
Section: Discussionmentioning
confidence: 70%
“…Several reports have shown that MSCs have the ability to interfere with DC differentiation and maturation, from both CD34 + bone marrow cells and CD14 + monocytes. 35,36 In this study we have shown that co-culturing of monocytes with UCMSCs prevented the CD14 + cells to differentiate and mature to DCs. Although the monocytes acquired antigens such as CD209, CD86 and B7-H1, all known to be expressed on imDCs, these cells failed to downregulate CD14 antigen in the presence of UCMSCs.…”
Section: Discussionmentioning
confidence: 70%
“…Several studies demonstrated previously that MSCs might interfere with the differentiation of CD34 1 HPC into mature DCs. 11,12 Recently, Li et al 30 showed that human bone marrow-derived MSCs may induce HPCs to generate regulatory DCs through activation of the Notch pathway. Liu et al 11 reported that embryonic fibroblast-derived MSCs induced generation of mouse regulatory DCs from HPCs by activation of SOCS3 in a IL-10-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recently, several groups reported that MSCs may drive the differentiation of regulatory DCs from HPCs. 11,12 However, the underlying mechanisms are still poorly understood and the induction of regulatory DCs in vivo remains controversial.…”
mentioning
confidence: 99%
“…Human MSCs suppress the proliferation of T cells through mediators such as TGF-β and HGF [125], and induce apoptosis of activated T cells through indoleamine 2,3-dioxygenase secretion [126]. MSCs also interfere with dendritic cell differentiation [127][128][129], which is crucial for the production of pro-inflammatory cytokines-including TNF-α, IFN-γ and IL-12-as well as B-and NK-cell proliferation [130,131]. This markedly hampers the normal inflammatory function of immune cells (Fig 2).…”
Section: Msc-mediated Immunomodulation In Metastasismentioning
confidence: 99%